If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A = 3b + -15 Reorder the terms: A = -15 + 3b Solving A = -15 + 3b Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Simplifying A = -15 + 3b
| 3x(x)=3x-2 | | u=181+21(6) | | 12-24x=4 | | 2m=2.2 | | 7m-11m=36 | | 64x^2=-1 | | 6x-8+2=2x+12+9x | | 4(x+2)=8(x-7) | | 9(7.2)= | | (-4b^3)(2b^5)= | | 15x+0.4y+2z-19.1+3x+10y-z-23.25=90 | | 6w^2+7w+2=0 | | X+28.25=44.00 | | 6x+13y=56 | | 5+2x=2x+6b | | 16x-2=15x | | 49-x=291 | | 36=3x(x)-3x-2(x-2) | | X-14.25=27.50 | | (-7x^4y^2)(-2x^3y)= | | 8t=90-2t | | -3+4x=3x+4 | | 2(-5+7x)=-1-2(1-7x) | | 640=4*130+n | | P+1.7=6.0 | | 5(5-2x)-6(2-x)=7(1x) | | -u+234=147 | | X^2+10x+7=-10 | | 6sin(2x)-3=0 | | 2x+2+3x-3+12=180 | | 3(3-d)-(-2)(d-3)=-(2d-5) | | ln(2x)-ln(x+2)=-1 |